2014
DOI: 10.2217/pme.13.107
|View full text |Cite
|
Sign up to set email alerts
|

’Personalized Medicine’: What’S in a Name?

Abstract: Over the last decade genomics and other molecular biosciences have enabled new capabilities that, according to many, have the potential to revolutionize medicine and healthcare. These developments have been associated with a range of terminologies, including 'precision', 'personalized', 'individualized' and 'stratified' medicine. In this article, based on a literature review, we examine how the terms have arisen and their various meanings and definitions. We discuss the impact of the new technologies on diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 45 publications
0
79
0
Order By: Relevance
“…Using personalization in clinical care can be simple and inexpensive to administer, such as targeting a screening program based on a family history. A study performed by Hovell et al in the 1980s demonstrated the value of such simple interventions in the management of hypertension, and emphasized the importance of 'personalized care,' which is not to be confused with its subset of 'personalized (genomic) medicine' [24,25]. In the quasi experimental design in this study, patients were managed either with specialized, individualized attention, which included courteous service and appointments, made at the patient's convenience.…”
Section: Treatment Strategiesmentioning
confidence: 97%
“…Using personalization in clinical care can be simple and inexpensive to administer, such as targeting a screening program based on a family history. A study performed by Hovell et al in the 1980s demonstrated the value of such simple interventions in the management of hypertension, and emphasized the importance of 'personalized care,' which is not to be confused with its subset of 'personalized (genomic) medicine' [24,25]. In the quasi experimental design in this study, patients were managed either with specialized, individualized attention, which included courteous service and appointments, made at the patient's convenience.…”
Section: Treatment Strategiesmentioning
confidence: 97%
“…, Pokorska‐Bocci et al . ). Indeed, most social science work on personalised medicine has associated the latter with pharmacogenomics or pharmacogenetics.…”
Section: Introductionmentioning
confidence: 97%
“…, Pokorska‐Bocci et al . ), among researchers working in the field, nanomedicine is frequently understood as matching ‘the right drug to the right patient and in some cases even to design the treatment for a patient according to genotype as well as other individual characteristics’ (Jain : 1). The question left open by this definition is the precise meaning of ‘individual characteristics’.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The cost alone to the US economy could be up to $30 billion per annum, not to mention the very significant human suffering and loss. [3--6] Personalised medicine, also known as Precision Medicine or Stratified Medicine, [7] seeks to avoid these issues through the development of methodologies that enable clinicians to know in advance of dosing which drugs will be both efficacious and safe in their patients. Pharmacogenomics is focused on the prediction of the effects of drugs on the body, and conversely, of the effects of the human body on the drug, through the use of genomic profiling.…”
Section: Introductionmentioning
confidence: 99%